Arc evaporated Ti-Al-N/Cr-Al-N multilayer coating systems for cutting applications. (April 2018) - Teppernegg, T.; Czettl, C.; Michotte, C.; Mitterer, C.
Abstract: Ti-Al-N based coatings are presently state-of-the art for severe cutting applications. Further improvement of these coatings can be reached by multilayer architectures in combination with different layer materials. Within this work, multilayer arrangements consisting of Ti-Al-N and Cr-Al-N sublayers with different chemical composition and sublayer thicknesses were investigated. All coatings were deposited via cathodic arc evaporation. The individual sublayers of the multilayer coatings exhibited thicknesses of 10, 30, 100 and 300 nm, respectively. The morphology and microstructure of the coatings were investigated by scanning and transmission electron microscopy and X-ray diffraction. Mechanical properties were evaluated using nanoindentation and milling tests. In addition, the thermal stability of the coatings was characterized by annealing experiments. An optimum in hardness and cutting performance was obtained for multilayers with 10 nm sublayer thickness and high Al contents within the Ti-Al-N layers, whereas the Al content in the Cr-Al-N sublayers showed only a minor effect. Highlights: Ti-Al-N & Cr-Al-N multilayered coatings with individual Al content in sublayers investigated. All coatings exhibit columnar morphology with single phase fcc Ti-Al-N & Cr-Al-N structure. Maximum hardness detected in coatings with a high Al content in Ti-Al-N sublayer. After annealing hardness slightly increases up to 600 °C - above 1000 °C significant drop. Decomposition of metastable Ti-Al-N and Cr-Al-N phase above 900 °C. Multilayered coating with high Al content in the Ti-Al-N sublayer shows best milling performance.